PENGARUH BEBAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN MELALUI SEMANGAT KERJA SEBAGAI VARIABEL INTERVENING - Natalia, Silvia; Harini, Sri; Ismartaya (Jurnal Visionida, 2025)
The purpose of this study is to determine employee responses and analyze the direct and indirect influence of workload, competence on performance through work morale as an intervening variable in the production division of PT. Tirta Fresindo Jaya Bogor. The number of samples in this study was 100 respondents. This study is a quantitative study with a descriptive and verification research design. The data collection procedure in this study uses literature studies and field studies. In this study the author uses path analysis data analysis techniques, data testing using the SPSS version 31 program. The results of the study indicate that employee responses to workload, competence, work morale and performance are in the high category. Meanwhile, the results of the hypothesis test prove that workload and competence have a direct positive and significant effect on work morale; workload and competence have a direct positive and significant effect on performance; work morale has a direct positive and significant effect on performance and; work morale is able to mediate workload and competence on performance.